Analisis Spasial dan Temporal Temperatur Permukaan Gunung Api Ruang Menggunakan Citra Satelit Landsat 8 Tirs - Believe Vidnel Rampi; Cyrke Adfie Netty Bujung; Alfrie Musa Rampengan (Jurnal FisTa Fisika dan Terapannya, 2026)
Indonesia is the country with the most mountains. The number of volcanoes in Indonesia is around 500. Of these, 129 are active volcanoes. This study aims to map the distribution of temperature and determine the direction of surface heat flow of Ruang Volcano before an eruption. This research was conducted by temporally analyzing the temperature distribution in Ruang Volcano to predict the direction of geological structure openings in the area using remote sensing methods. The analysis was carried out temporally using thermal infrared band 10 image data to determine the direction of heat flow according to the resulting distribution map. The analysis results show that the surface temperature distribution map of Ruang Volcano before the eruptions in 2015, 2019, and 2024 shows a similar pattern. Based on the surface temperature distribution map of Ruang Volcano, the direction of flow before the eruption comes from the northeast.